Analisis Perlakuan Aset Tetap PSAP No. 07 Tahun 2010 di Kantor Desa Sumber Makmur - Fatimah, Nor Siti; Bandi, Maulida Hirdianti; Nurmalina, Radna (CV. Doki Course and Training, 2024)
Abstract : This study aims to analyze the treatment of fixed assets in accordance with Government Accounting Standards Statement No. 07 of 2010 concerning assets at Sumber Makmur Village Office, Takisung District. This research was conducted to see the suitability of the application of Government Accounting Standard No. 07 of 2010 in the implementation of village fixed asset management for Fixed Asset Recognition, Measurement, Subsequent Measurement at Initial Valuation, and Recognition of Fixed Assets. The analysis method used is descriptive qualitative. The data used in this study are the Inventory Report (LHI) and the Village Asset Inventory Book for 2021, 2022, and 2023. Data collection techniques are collected through literature study, interviews, and documentation. The results showed that the treatment of PSAP No. 07 of 2010 at Sumber Makmur Village Office was not maximized in its implementation due to a lack of understanding of these accounting standards and difficulties in integrated fixed asset management. So that there is still recognition of assets that are not appropriate, have not depreciated assets, journalized assets after they are obtained, and has not present fixed assets owned in the Village Property Report or Balance Sheet. Abstrak : Penelitian ini bertujuan untuk menganalisis perlakuan aset tetap sesuai dengan Pernyataan Standar Akuntansi Pemerintah No. 07 Tahun 2010 tentang aset pada Kantor Desa Sumber Makmur Kecamatan Takisung. Penelitian ini dilakukan untuk melihat kesesuaian penerapan Standar Akuntansi Pemerintah No. 07 Tahun 2010 dalam pelaksanaan pengelolaan aset tetap desa untuk Pengakuan, Pengukuran, Pengukuran Selanjutnya pada Penilaian Awal, dan Pengakuan Aset Tetap. Metode analisis yang digunakan adalah deskriptif kualitatif. Data yang digunakan dalam penelitian ini adalah Laporan Inventaris (LHI) dan Buku Inventaris Aset Desa tahun 2021, 2022, dan 2023. Teknik pengumpulan data dilakukan melalui studi pustaka, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa perlakuan PSAP No. 07 Tahun 2010 di Kantor Desa Sumber Makmur belum maksimal dalam pelaksanaannya karena kurangnya pemahaman terhadap standar akuntansi tersebut dan kesulitan dalam pengelolaan aset tetap secara terpadu. Sehingga masih terdapat pengakuan aset yang tidak sesuai, belum melakukan penyusutan aset, menjurnal aset setelah diperoleh, dan belum menyajikan aset tetap yang dimiliki dalam Laporan Harta Desa atau Neraca..